Comparing the Impact of Course-Based and Apprentice-Based Research Experiences in a Life Science Laboratory Curriculum - Casey Shapiro (American Society for Microbiology, 2015)
This four-year study describes the assessment of a bifurcated laboratory curriculum designed to provide upper-division undergraduate majors in two life science departments meaningful exposure to authentic research. The timing is critical as it provides a pathway for both directly admitted and transfer students to enter research. To fulfill their degree requirements, all majors complete one of two paths in the laboratory program. One path immerses students in scientific discovery experienced through team research projects (course-based undergraduate research experiences, or CUREs) and the other path through a mentored, independent research project (apprentice-based research experiences, or AREs). The bifurcated laboratory curriculum was structured using backwards design to help all students, irrespective of path, achieve specific learning outcomes. Over 1,000 undergraduates enrolled in the curriculum. Self-report survey results indicate that there were no significant differences in affective gains by path. Students conveyed which aspects of the curriculum were critical to their learning and development of research-oriented skills. Students’ interests in biology increased upon completion of the curriculum, inspiring a subset of CURE participants to subsequently pursue further research. A rubric-guided performance evaluation, employed to directly measure learning, revealed differences in learning gains for CURE versus ARE participants, with evidence suggesting a CURE can reduce the achievement gap between high-performing students and their peers.